Acute Carbamazepine Intoxication - María Dolores Calabria Gallego; Mónica Alañá García (MDPI AG, 2022)
Carbamazepine is an anticonvulsant drug with multiple mechanisms of action, which condition the presence of a characteristic clinical picture after the overingestion of the drug. We expose a case report about a patient who, in the context of an attempted suicide, presented acute intoxication by benzodiazepines and carbamazepine, presenting the characteristic clinical picture of fluctuations in the level of consciousness, even presenting gaze deconjugation, almost unreactive coma and generalized hypotonia.